(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study investigates the relationship between dental prosthesis materials and the composition of oral microflora among 80 adult patients using different prosthesis types: removable acrylic, fixed metal-ceramic, zirconia-based, and titanium implant-supported restorations. Standardized clinical examinations, microbiological cultures, and quantitative PCR analyses were performed to assess microbial diversity, load, and surface characteristics. The results showed that acrylic resin dentures harbored the highest microbial load (45.6×10^5 CFU/mL) dominated by Candida albicans and Streptococcus mutans, while zirconia and titanium prostheses exhibited reduced biofilm formation and higher microbial diversity (Shannon index 2.10). Surface roughness strongly correlated with total microbial load (r=0.89). These findings underscore that smoother materials such as zirconia and titanium minimize microbial accumulation, reducing the risk of denture stomatitis, secondary caries, and peri-implant inflammation. Clinically, the study highlights the importance of material selection, finishing protocols, and individualized hygiene programs to enhance prosthesis longevity and oral health outcomes.